2023
DOI: 10.1002/anie.202217374
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Reduction of Metal–Organic Frameworks for Enhanced Cryopreservation of Red Blood Cells

Abstract: To increase the red blood cell (RBC) cryopreservation efficiency by metal-organic frameworks (MOFs), a dimensional reduction approach has been proposed. Namely, 3D MOF nanoparticles are progressively reduced to 2D ultra-thin metal-organic layers (MOLs). We found that 2D MOLs are beneficial for enhanced interactions of the interfacial hydrogenbonded water network and increased utilization of inner ordered structures, due to the higher surface-to-volume ratio. Specifically, a series of hafnium (Hf)-based 2D MOLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Cryopreservation of cells is a vital technique in various fields, including regenerative medicine, , supplying transfusion, , cellular therapy, , and biobanking within both plants and animals. Cryopreservation allows long-term storage and transportation of cells while maintaining their viability and functionality. Therefore, cryoprotectants to preserve cultured cells through freezing have been the subject of extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreservation of cells is a vital technique in various fields, including regenerative medicine, , supplying transfusion, , cellular therapy, , and biobanking within both plants and animals. Cryopreservation allows long-term storage and transportation of cells while maintaining their viability and functionality. Therefore, cryoprotectants to preserve cultured cells through freezing have been the subject of extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of materials science and nanotechnology, some researchers have devoted effort to exploring novel deicing nanomaterials for cell cryopreservation, including carbon dots, 22 metal−organic frameworks (MOFs), 23,24 two-dimensional (2D) nanomaterials, 25−30 and other nanomaterials. 31,32 Among them, 2D nanomaterials have a wide range of applications in the fields of energy and biology due to their unique structure (functional groups and large specific surface area) and excellent catalytic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of materials science and nanotechnology, some researchers have devoted effort to exploring novel deicing nanomaterials for cell cryopreservation, including carbon dots, metal–organic frameworks (MOFs), , two-dimensional (2D) nanomaterials, and other nanomaterials. , Among them, 2D nanomaterials have a wide range of applications in the fields of energy and biology due to their unique structure (functional groups and large specific surface area) and excellent catalytic and optical properties. Recently, 2D materials have attracted more attention in the field of cell cryopreservation among these anti-icing materials. , For example, Wang et al studied the inhibitory effect of graphene oxide nanosheets (GO NSs) on ice crystals in cell cryopreservation and found that GO NSs could be adsorbed onto the surface of ice crystals and played a critical role in modifying the morphology of ice crystals and controlling the growth of ice crystals . In addition, GO NSs and MOS 2 nanosheets also exhibited significant photothermal effects under near-infrared irradiation and were successfully applied to the rapid recovery of frozen cells, improving cell survival .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the calixarene backbone is a three-dimensional (3D) structure and possesses a unique macrocycle cavity, which may be profitable to enhance the interfacial hydrogen-bond interactions with water due to the high surface-to-volume ratio. 13,14 Sulfoxide-based calixarene derivatives 15 are well-studied supramolecular hosts, which are constructed by repeating building blocks and possess the unique properties of a well-defined 3D structure, controllable conformation and pre-organized scaffold, and have garnered tremendous applications in drug delivery, biosensing and bioimaging. However, a study on the cryopreservation of cells based on sulfoxidemodified calixarene derivatives has not been reported.…”
mentioning
confidence: 99%